Clinical and analytical evaluation of the new Aptima Mycoplasma genitalium assay, with data on M. genitalium prevalence and antimicrobial resistance in M. genitalium in Denmark, Norway and Sweden in 2016. (May 2018) - Unemo, M.; Salado-Rasmussen, K.; Hansen, M.; Olsen, A.O.; Falk, M.; Golparian, D.; Aasterød, M.; Ringlander, J.; Nilsson, C. Stezckó; Sundqvist, M.; Schønning, K.; Moi, H.; et al.
Abstract: Objectives: Mycoplasma genitalium (MG) causes urethritis and cervicitis, potentially causing reproductive complications. Resistance in MG to first-line (azithromycin) and second-line (moxifloxacin) treatment has increased. We examined the clinical and analytical performance of the new Conformité Européene (CE)/ in vitro diagnostics (IVD) Aptima Mycoplasma genitalium assay (CE/IVD AMG; Hologic); the prevalence of MG, Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG); and MG resistance to azithromycin and moxifloxacin in Denmark, Norway and Sweden in 2016. Methods: From February 2016 to February 2017, urogenital and extragenital (only in Denmark) specimens from consecutive attendees at three sexually transmitted disease clinics were tested with the CE/IVD AMG, the research-use-only MG Alt TMA-1 assay (Hologic), Aptima Combo 2 (CT/NG) assay and a laboratory-developed TaqMan real-time mgp B quantitative real-time PCR (qPCR). Resistance-associated mutations were determined by sequencing. Strains of MG and other mycoplasma species in different concentrations were also tested. Results: In total 5269 patients were included. The prevalence of MG was 7.2% (382/5269; 4.9–9.8% in the countries). The sensitivity of the CE/IVD AMG, MG Alt TMA-1 and mgp B qPCR ranged 99.13–100%, 99.13–100% and 73.24–81.60%, respectively, in the countries. The specificity ranged 99.57–99.96%, 100% and 99.69–100%, respectively. The prevalence of resistance-associated mutations for azithromycin and moxifloxacin was 41.4% (120/290; 17.7–56.6%) and 6.6% (18/274; 4.1–10.2%), respectively. Multidrug resistance was found in all countries (2.7%; 1.1–4.2%). Conclusions: Both transcription-mediated amplification (TMA)-based MG assays had a highly superior sensitivity compared to the mgp B qPCR. The prevalence of MG and azithromycin resistance was high. Validated and quality-assured molecular tests for MG, routine resistance testing of MG-positive samples and antimicrobial resistance surveillance are crucial.